The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jaip.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy Sensitization and Presentation in Siblings of Food Allergic Children

Abstract: Background Many parents of food allergic children have concerns about the development of food allergies in their other children. Objective We sought to determine prevalence of food sensitization and clinical food allergy among siblings of food allergic children. Methods Two thousand eight hundred and thirty-four children were enrolled in the Chicago Family Cohort Food Allergy study. One thousand one hundred and twenty children (ages 0–21 years) with a food allergy (defined by a reported reaction history an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…However, thresholds are less useful for intermediate values where there is already a doubt whether the patient is truly allergic ( 12 21 ), and may be associated with false positives ( 10 , 22 ). Children in particular have a higher rate of sensitization without true allergy ( 23 ). Other biomarkers that have been explored include basophil activation tests (BATs) as well as the measurements of allergen-specific IgG, total IgE (tIgE), and component resolved diagnostics, but definitive thresholds remain to be established ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, thresholds are less useful for intermediate values where there is already a doubt whether the patient is truly allergic ( 12 21 ), and may be associated with false positives ( 10 , 22 ). Children in particular have a higher rate of sensitization without true allergy ( 23 ). Other biomarkers that have been explored include basophil activation tests (BATs) as well as the measurements of allergen-specific IgG, total IgE (tIgE), and component resolved diagnostics, but definitive thresholds remain to be established ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…While allergen‐specific IgE is commonly used to diagnose food allergies, many patients with allergen‐specific IgE in the blood do not react upon consumption of that food . In this study, while cow's milk‐specific IgE was significantly decreased in the serum of NE‐immunized mice at the end of the study, IgE titers remained significantly elevated to similar levels where sensitized control (non‐NE vaccinated) mice reacted to challenge.…”
Section: Discussionmentioning
confidence: 67%
“…Gupta et al 54 evaluated the risk of food sensitization and allergy for siblings of a proband with food allergy. They evaluated 1120 children with food allergy with at least 1 sibling and found that 66.6% of the siblings were food sensitized but only 13.6% were clinically reactive.…”
Section: Risk Factorsmentioning
confidence: 99%